Economic voting in Portugal, 2002–2009 - Freire, A.; Santana-Pereira, J. (Electoral Studies, 2012)
This article tests the economic voting hypothesis in Portugal during the three most recent first-order elections (2002, 2005, 2009), trying to make sense of the multiplicity of choices in the Portuguese party system. We observed that positive sociotropic perceptions increase the probability to vote for the incumbent, even when we control for long-term factors of vote choice; egotropic effects are weaker. Negative economic perceptions not only lead to a higher probability to vote for the major opposition party, but, in some cases, increase the probabilities to vote for small parties or to refrain from voting. Sociotropic effects are actually quite constant in this timeframe, but their strength to explain the vote is lower than that of ideology and (before 2009) religiosity.